PENGEMBANGAN PRODUK OLAHAN IKAN DI DESA TUING MELALUI PENINGKATAN KUALITAS PACKAGING DAN PELATIHAN DIGITAL MARKETING - Yanto Yanto; Duwi Agustina; Suhaidar Suhaidar (Universitas Mataram, 2023)
Tuing Village is a village in Bangka Regency which is famous for its natural products in the form of sea fish. Currently, sea fish caught by the people of Tuing Village are processed into processed foods such as fish balls, pempek, and salted fish. However, the problem is that the people of Tuing Village have not properly packaged their processed marine fish products. In addition, their products have not been marketed to other areas in Bangka district. Therefore, we think it is important to provide knowledge about improving product quality and digital marketing training to the people of Tuing Village. The implementation of improving the quality of packaging and digital marketing training uses two stages, namely the preparation and implementation stages of activities. The stages of implementing the activity are divided into two, namely socialization and training activities. Results: The people of Tuing Village can understand the importance of improving the quality of packaging for their processed products. This important information is obtained as long as they participate in the socialization and training that we provide regarding the importance of the quality of product packaging to the durability of the product inside. Apart from that, the people of Tuing Village also understand the importance of marketing through digital marketing to reach more potential consumers, especially in the Bangka Belitung Islands Province. Conclusion: The conclusion of this activity is: increasing the skills of the Tuing village community in the form of using digital marketing and improving the quality of product packaging.